Diagnostic value of the gingival cytogram in school-age children suffering from chronic gastritis and duodenitis - Romanenko, Ye.G.; Komskyi , M.P.; Titov, O.H.; Bureha , I.Y.; Khotimska , Yu.V.; Lavreniuk , Ya.V.; Alieksieienko, V.V.; Holub , A.V. (Medicni Perspektivi, 2024)
In recent years, there has been an increase in the incidence of morbidity associated with digestive organ pathology in the pediatric population. The oral cavity is the digestive tract opening, sharing a common ectodermal origin with it. The changes in the cytogram of the oral mucous membranes can signal about exacerbation of pathological processes in the gastrointestinal tract. The aim of this work: to identify the features of gingival cellular composition in school-age patients with chronic gastritis and duodenitis in order to improve diagnostic methods at the disease stages. Examinations of the gingival cytogram in children aged 12-17 years with chronic gastritis and duodenitis (27 individuals with the disease in acute stage, 30 – in remission) were carried out. The control group included 28 children who did not have any somatic pathology by the results of the examination. For cytological examination, imprint smears from the gingival vestibular surface of the upper and lower jaws were made. The smears were fixed and stained by the May-Grunwald Pappenheim method, and then examined using a microscope with an immersion system. The percentage of epithelial cells and connective tissue cells was calculated per 100 cells. The number of pathologically altered epithelial cells was determined: with vacuolated cytoplasm, with nucleus deformation. In children with chronic gastritis and duodenitis disorders in the gingival cellular composition with a predominance of dystrophic components were found, that was manifested by a decrease in the proportion of epithelial cells at terminal stages of differentiation, an increase in the proportion of cells with cytopathological phenomena, polymorphonuclear leukocytes and lymphocytes. Changes in the cytogram were especially expressed in the phase of disease exacerbation. Knowing the phases of the wound process, based on the timing and sequence of the cellular ensembles seen in the cytogram, it is possible to control the disease periods, and timely apply measures to prevent exacerbations. This diagnostic method is especially indicated for children who have relative and absolute contraindications for fibroesogastroduodenoscopy.